Academicians' awareness, attitude, and use of open access during the COVID-19 pandemic. (September 2022) - Turgut, Yigit Emrah; Aslan, Alper; Denizalp, Nuran Varlı
The aim of this research is to reveal academics' awareness, attitude, and use of open access. In line with the research purpose, the survey research design is adopted. This research consists 151 academics from 12 basic research areas; eight of them being Professor Dr, 17 being Associate Professor Dr, 49 being Doctor Lecturer, and 77 being Research Assistant or Lecturer. A questionnaire consisting of 19 open access and five demographic information questions was used for the data collection tool. The research results show that 75% of the academics have open access awareness and that their awareness is generally created by information that they obtain through the Internet and their friends. In addition, most of the academics indicate that their awareness of open access has increased during the pandemic period. When considering the level of academics' use of open access, it is found that 75% of the academics use articles in open access journals for their own research and 51% of the academics do not publish any articles in open access journals.